Satisfied Result of Modified Knapp Procedure for A Rare Case of Isolated Superior Rectus Muscle Rupture - Gusti Guardana; Lasmida Ruth Simatupang (Majalah Oftalmologi Indonesia, 2021)
Purpose: To report a successful management of strabismus after isolated superior rectus muscle rupture with modified Knapp procedure. Case Description: A 23-year-old patient with chief complain of having double vision since 6 days. He had history of falling and his right eye hit the floor. After that, he had double vision and his right eye could not move normally to the right and up gaze. Ophthalmology examination of right eye, uncorrected visual acuity was 6/12 and not improved with pinhole. He had 15 PD esotropia and right hypotropia on Hirschberg test. Right eye movement was restricted to to lateral, superotemporal and superonasal (-3 on abduction and elevation). The superior rectus muscle was barely visible at superior part of orbit. However, Computed Tomography scan showed there was not any enlargement of the extra ocular muscles. He had exploration surgery and intraoperatively the superior rectus muscle could not be identified. Surgeon decided to do modified Knapp procedure. On the third week and second month of follow up, patient did not have any complain of diplopia and no vertical and horizontal deviation. Conclusion: Isolated superior rectus muscle rupture is a rare case. A thorough patient’s history, ophthalmology and imaging technique are needed to establish the etiology. Modified Knapp procedure gave a satisfied result in this case to treat the esotropia and hypotropia.